Meningkatkan Kemampuan Computational Thinking Siswa Sekolah Dasar Menggunakan Lembar Aktivitas Unplugged Coding dalam Pembelajaran Matematika - Marito, Winanda; Riani, Nova (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to improve the computational thinking (CT) skills of elementary school students through unplugged coding activity sheets in mathematics learning. The research uses a quantitative approach with a One Group Pretest-Posttest Design pre-experimental design. The subjects of the study are 25 fourth-grade students from Muhammadiyah 18 Medan, selected through purposive sampling. Data was collected using a CT ability test administered before and after the learning session. Data analysis was conducted using a paired sample t-test and N-Gain calculation. The research results show a significant increase in students' CT ability with an average score rising from 54.48 (pre-test) to 73.32 (post-test), a t-statistic value of -86.782, and a significance level of 0.000 (p < 0.05). The N-Gain value of 0.65 indicates the effectiveness of learning in the medium category. All CT indicators showed improvement, with generalization experiencing the highest increase (39.6%), followed by decomposition (39.3%), abstraction (38.9%), and algorithmic thinking (38.6%). However, the debugging and iteration indicators showed relatively lower increases of 28.7% and 23.6%, respectively. This research demonstrates that mathematics learning with unplugged coding activity sheets can be a solution to develop the CT abilities of primary school students with limited technological devices.